Data Analyses using the Action Project Method Coding Technique: A Guide. (8th June 2022) - Jensen, Charlotte; Hoben, Matthias; Chamberlain, Stephanie A.; K. Marshall, Sheila; Young, Richard A.; Gruneir, Andrea
The qualitative action-project method (A-PM) was developed in counseling psychology and is useful for studying human actions in various contexts. With this article we provide a guide to A-PM data analysis with a focus on the method's coding technique. We briefly outline the theory underpinning the method as well as the different phases of data collection. The A-PM data analysis happens in parallel from a bottom-up and top-down approach, where researchers consider the data closely for what participants are doing, how they are doing it and the ways in which their actions are directed by their overall goals. We add to the existing literature by detailing the coding technique, providing examples at each stage of analysis, as well as reflect on the possibilities for adapting the protocol for different types of research. Our aim is to support researchers in their efforts to undertake the method.